O debate sobre o conceito de pessoa no tema dos transplantes de órgãos e tecidos: desafios bioéticos para o aconselhamento pastoral - Bergesch, Karen (2006)
The present paper intends to approach the concept of person in the interdisciplinar context of Bioethics, focusing on Pastoral Counseling. Therefore, it uses the theme of organ transplantation as framework. By studying the reality of organ transplantation as it is currently presented by disciplines such as Medicine, Law and Philosophy, the Pastoral Counseling updates its Theological practice of supporting people who are involved in the process of transplantation and their families. This demands the knowledge of their fears as well as of all necessary cares, which vary according to the different stages of transplantation. The first chapter proposes an approach of the reality of transplantation through 4 different cases. The second chapter presents the current debate about the concept of person, according to 5 different schools, as it takes place in Bioethics, and according to Christian Anthropology. The third chapter goes into the Brazilian law regarding the issue of transplantation. The last chapter, once enriched by the precedent discussions, develops a Practical-Theological contribution to the issue of transplantation by means of the concept of Therapeutic Community. The person is a capital concept and therefore it must be constantly updated in time and space in order that human dignity can be respected.